Effect of STEM picture book (shape by shape) and play-game interventions on early mathematics achievement among preschool children in Kota Kinabalu, Sabah, Malaysia - Connie Cassy Ompok; Qinghua Liu; Alley Emison; Norbert Bin Micheal Ligin; Noraina binti Noraidi (Journal of Electrical Systems, 2024)
In the field of early childhood education, there has been a lot of interest in preparing young children for mathematics instruction. The purpose of this study was to identify and compare the effects of the STEM Picture Book (Shape by Shape) and Play-Game Intervention using Augmented Reality on Early Mathematics Performance. The instrument used in this research was the Early Mathematics Achievement Test (TEMA) which was adapted from Ginsburg and Baroody (2003) and, Doig and Ompok (2010), based on the National Standard Preschool Curriculum Malaysia 2017. In this study, 50 preschoolers from national preschools in Kota Kinabalu, Sabah, participated in a quantitative quasi-experimental design. Before the intervention, the results of the independent t-test revealed no significant difference in early mathematics achievement between the control and treatment groups (p=.20). However, the paired t-tests demonstrated significant improvements in early mathematics achievement between the control group (p=.00) and treatment group (p=.00) before and after the intervention. The independent t-test showed a significant difference in early Mathematics achievement between the control and treatment groups (p=.01) after the intervention. Overall, the findings indicate that the STEM Picture Book (Shape by Shape) and Play-Game Intervention significantly enhance early Mathematics achievement compared to conventional teaching methods. These findings provide educators with practical guidance on how to incorporate cutting-edge technology, such augmented reality, which has the potential to create an immersive and dynamic learning environment.